THE HISTORY OF THE CREATION OF CHEMICAL WEAPONS,THE CHARACTERISTICS OF COMBAT USE AND THE INFLUENCE OF IT ON HUMAN BODY (Scientific journal of the Fergana State University, 2023)
This article provides information on the main types of weapons of mass destruction – chemical weapons, on the history of this creation, on its use in combat operations and on its negative impact on the human body.